Mini Tinjauan Literatur Pemanfaatan Aplikasi Macaulay untuk Berpikir Komputasi Siswa - Roslina Sahara; Yahfizham Yahfizham (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to examine the use of Macaulay2 software in improving students' computational thinking skills in mathematics learning, especially in abstract algebra material. Macaulay2 as an open-source Computer Algebra Sistem (CAS) provides a symbolic and algorithmic environment that encourages logical and systematic exploration of mathematical concepts. Literature reviews show that the use of Macaulay2 can strengthen conceptual understanding, train computational thinking, and introduce mathematical programming to students. However, technical challenges, limited Indonesian language teaching materials, and limited educational infrastructure are obstacles that need to be overcome through collaboration between educational stakeholders.